Isokinetic strength of shoulder internal and external rotators in cricket bowlers - X.M. Mabasa; A. Stewart; C. Fleishman (AOSIS, 2002)
The strength of the shoulder internal and external rotators incricket bowlers, may not be sufficient to cope with the demands of bowling.As very little research has been done on cricketers, this study was done to establish the isokinetic strength profile of the shoulder internal andexternal rotators in cricket bowlers.Isokinetic, shoulder rotational strength was evaluated in thirty malecricket volunteers with a mean age of 23.9 years and mean body weight of 70.3 kgs. The Cybex 340 dynamometer multi joint system was used to collect data on shoulder rotation strength in a standing neutral position. Data were collected at four different speeds (60,90,180 and 300deg/sec) and were computed for peak torque values for internal and external ratios for both dominant and non dominant shoulders.The results showed no statistically significant difference in the mean shoulder rotational torque between the bowlingand non-bowling shoulders for external rotation (p>0.05), and indicated statistically significant differences in themean shoulder rotational torque between the bowling and non-bowling shoulders for internal rotation (p<0.05). Therewas a significant decrease in isokinetic peak torque production for the external/internal rotator muscles as the speedof contraction increased (p<0.05). The peak torque ratio for the external/internal rotator muscles of the bowling armwere significantly less than of the non-bowling arm (p<0.05). These findings suggest that the strength ratios of thebowling arm need to be considered when managing young cricketers and their injuries.